Amiodarone-Associated Optic Neuropathy - Weidmayer, Sara L. (Canadian Journal of Optometry, 2018)
A 72-year old male presented symptomatic for unilateral inferior visual field loss, but was found to have bilateral optic neuropathy. Clinical features, an extended minimally symptomatic course and a temporal relationship to amiodarone use implicated amiodarone-associated optic neuropathy. Serial ancillary testing analyses provided insight into this entity’s natural course. This patient developed the greatest retinal nerve fiber layer thinning in the inferior quadrant; this may correlate with anatomically larger-diameter axons, supporting a previous publication which suggested that larger-diameter optic nerve axons are more susceptible to amiodarone-induced lipidosis. While rare, amiodarone-associated optic neuropathy may develop and cause permanent loss of visual function.